Long-Term Suicide Risk in Anxiety—The Lundby Study 1947–2011. Issue 3 (2nd July 2016) - Anderberg, Johan; Bogren, Mats; Mattisson, Cecilia; Brådvik, Louise
Abstract : The objective of this study was to calculate the long-term risk of accomplished suicide in anxiety disorders, and to compare this with a healthy population. The Lundby Study is a prospective, longitudinal cohort study on a population of 3, 563 subjects. Between 1947 and 1997, anxiety disorders were diagnosed in 300 subjects. Up to 2011 there were 68 suicides in all. The suicide risk was 3.3% for anxiety. For only anxiety, risk was increased (p = 0.008), but other diagnoses had a higher risk (p = 0.0001) compared with no diagnosis. Mean time from onset to suicide was 27 years. Risk of suicide in anxiety disorders seems elevated at an intermediate level. Suicide often occurs many years after onset of the disorder.